Development of Strawberry gummy jelly with reduced sugar content from Strawberry syrup - Takeungwongtrakul, S.; Thavarang, P.; Sai-Ut, S. (International Journal of Agricultural Technology, 2020)
The strawberry syrup from frozen strawberries industry was acidic and a red color. °Brix value of strawberry syrup was 26.77. It was used for preparation of strawberry gummy jellies. The suitable basic recipe of strawberry gummy jelly was selected.The result indicated that using 100% concentrated strawberry syrup in strawberry gummy jelly had the highest consumer acceptance. The sucrose was replaced by sucralose at the percentage of 0 25 50 75 and 100 (w/w). The result showed that using 50% sucralose for sucrose replacement in strawberry gummy jelly had the highest of consumer acceptance and lower calorie than control (sucrose). The replacement of sucrose by sucralose can be alternative ways of development of gummy jelly.